Enhancing Sustainability Awareness Through AI-Assisted Learning Videos on Environmental Pollution: A Study in Fourth Grade Elementary School - Oktaviani, Arzetia; Suratmi, Suratmi; Aswasulasikin, Aswasulasikin; Nurani, Dwi Cahaya (IJE : Interdisciplinary Journal of Education, 2025)
Technology integration is crucial for modern education. This study investigates the use of Artificial Intelligence (AI)-assisted learning videos to enhance sustainability awareness among elementary students, an area where awareness remains low according to PISA data. A quantitative survey method was employed, utilizing a Likert-scale questionnaire to assess three aspects of sustainability awareness (behavioral, emotional, and practical) among 19 fourth-grade students at SDN 156 Palembang after video intervention. Results indicated a high level of sustainability awareness with a mean score of 3.5 (on a 4-point scale) and an overall percentage of 87.73%. All three aspects scored highly (86-89.2%), falling into the 'habits that are often/always done' category. The study concludes that AI-assisted learning videos are an effective tool for significantly improving sustainability awareness and behaviors in young learners, offering an innovative solution for environmental education